Pengaruh Video Edukasi Penggunaan Suplemen Kesehatan saat Pandemi Covid-19 terhadap Tingkat Pengetahuan Masyarakat di Kecamatan Binawidya Pekanbaru - Husnawati - Husnawati; R. Pebliana Syahara; Seftika Sari; Putri Lestari (JURNAL FARMASI DAN MAKANAN, 2024)
The significant increase in confirmed cases of COVID-19 necessitates the implementation of preventive measures by the general public to mitigate the risk of contracting the disease. One strategy that can be employed involves the consumption of health supplements. Among the most prevalent health supplements consumed by the public during the COVID-19 pandemic is vitamin C, which is taken to enhance immunity as part of the preventive measures against COVID-19. This research aims to see the effect of providing educational videos on the use of health supplements during the COVID-19 pandemic on the level of community knowledge in the Binawidya sub-district of Pekanbaru. This research is a quasi-experimental research with a non-randomized control group pretest-posttest design with data collection techniques, namely purposive sampling using a Google form questionnaire. In this research, the sample consisted of individuals from the Binawidya sub-district who met the inclusion criteria, totaling 100 respondents. The analysis of the knowledge data revealed a significant impact of educational videos on the utilization of health supplements amidst the COVID-19 pandemic, as evidenced by an obtained P value of 0.000, which is less than the predetermined significance level of 0.05.